Cholera in the portuguese region of Alto Minho in the second half of the nineteenth century: epidemic outbreaks, treatment and behaviours - Araújo, Maria Marta Lobo de (2010)
[Excerpt] In the 19th century in result of the inherent advances of the industrializing process, the distances were shortened, distant regions became nearer and the circulation of people and goods through several parts of the globe was easier. The diseases also spread more quickly, assuming sometimes uncontrollable propor tions, not only by land, but also by sea, through boats that, in addition of trans porting people and goods, also served as means of transmission of epidemics into different countries and continents. I Along the 19th century cholera1 was one of the diseases that, both on land or by the sea, reached several areas of the European continent, causing a strong impact in the western civilization, not only in demographic and economical level, but also in social and cultural ones. The disruptions caused by the illness, aggravated by the incompetence initially revealed by the authorities to avoid and fight this pathology, contributed to the appearance of not much coherent and even imaginative explanations and theories, in the desperate attempt of finding justification and solution for an evil that was affecting all, direct or indirectly. As an example, in 1866, in the sequence of the epidemic outbreak of cholera, which emerged in Portugal in 1865, the newspaper O Vianense, published an article of the Gazette de France, where it is revealed the dis covery of cholera by a doctor, who stated the idea that the origins of the Asian cholera were connected with the emission of poisonous gases freed by the bodies that, thousands of years ago were burnt in India. These gases were concentrated in the sky of the tropics, lifted to the most elevated regions of the atmosphere during the day, but after the sunset, they descended to the inferior regions, in order to being mixed with the water and the food, penetrating the lungs through breathing. When this poisonous gas was introduced into body, it caused the very own symptoms of cholera, as dysentery, vomiting and cramps [2]. [...]